Advanced System Architecture and Algorithms for Smart Distribution Grids: The Sustainable Approach - André Madureira (2015)
In order to allow large scale integration of Distributed Energy Resources in a secure and efficient way, the EU Project SuSTAINABLE designed a reference architecture for management and control of the distribution system as a whole. This novel architecture is based on the hierarchical architecture already deployed in the InovGrid test site in Évora, Portugal InovCity. This will require the development of specific algorithms and tools to support distribution system operation that are able to exploit distributed intelligence in several network components. These advanced control functionalities are summarily described and include: state estimation, load and renewable energy forecasting and voltage control.